Persistence of high venous-to-arterial carbon dioxide difference during early goal-directed therapy could be related to multiorgan dysfunction in septic (2010)
Venous-to-arterial carbon dioxide difference (Pv-aCO2) may reflect the adequacy of blood flow during shock states. We sought to test whether the development of Pv-aCO2 during the very early phases of resuscitation is related to multi-organ dysfunction and outcomes in a population of septic shock patients resuscitated targeting the usual oxygen-derived and hemodynamic parameters.